2013
DOI: 10.47102/annals-acadmedsg.v42n3p138
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Guidelines on the Use of Opioids in Chronic Non-Cancer Pain—A Consensus Statement by the Pain Association of Singapore Task Force

Abstract: Introduction: While opioids are effective in carefully selected patients with chronic non-cancer pain (CNCP), they are associated with potential risks. Therefore, treatment recommendations for the safe and effective use of opioids in this patient population are needed. Materials and Methods: A multidisciplinary expert panel was convened by the Pain Association of Singapore to develop practical evidence-based recommendations on the use of opioids in the management of CNCP in the local population. This article d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 115 publications
0
6
0
2
Order By: Relevance
“…Prescription opioids are commonly prescribed both in primary care as well as in the emergency department for pain relief; and, although opioids are not as widely prescribed for non-cancer pain in Singapore, recent studies have shown an increase in opioid use in the country. [ 17 21 22 ] Benzodiazepines are also commonly administered to patients with anxiety or sleep disorders. Studies are required to further characterise the misuse of these drugs in Singapore, including determining the demographics of misusers, doses misused, frequency of misuse and the association of misuse with chronic pain, to further understand the potential risk of opioid and benzodiazepine dependence among high-risk groups of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prescription opioids are commonly prescribed both in primary care as well as in the emergency department for pain relief; and, although opioids are not as widely prescribed for non-cancer pain in Singapore, recent studies have shown an increase in opioid use in the country. [ 17 21 22 ] Benzodiazepines are also commonly administered to patients with anxiety or sleep disorders. Studies are required to further characterise the misuse of these drugs in Singapore, including determining the demographics of misusers, doses misused, frequency of misuse and the association of misuse with chronic pain, to further understand the potential risk of opioid and benzodiazepine dependence among high-risk groups of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] There have been concerns about increasing use of opioid analgesia in Singapore related to the potential for misuse and addiction; as a result, the Pain Association of Singapore convened a multidisciplinary expert panel in September 2011 to develop practical evidence-based recommendations on the use of opioids for the management of chronic non-cancer pain in Singapore. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Opioids that are commonly prescribed for pain relief include morphine, pethidine, oxycodone, fentanyl, hydromorphone, methadone, tapentadol, and tramadol. 17 There was limited evidence on the use of opioids as first-line treatment of chronic noncancer pain. Instead, opioids are used as a multimodal approach, preferably as second or third line of pain management.…”
Section: Singaporementioning
confidence: 99%
“…The aim of the association was to implement evidence-based recommendations on the use of opioids for managing chronic noncancer pain. Opioids that are commonly prescribed for pain relief include morphine, pethidine, oxycodone, fentanyl, hydromorphone, methadone, tapentadol, and tramadol 17. There was limited evidence on the use of opioids as first-line treatment of chronic noncancer pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation